Regression discontinuity designs based on population thresholds: Pitfalls and solutions - Andrew C. Eggers; Ronny Freier; Veronica Grembi; Tommaso Nannicini (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
In many countries, important features of municipal government (such as the electoral system, mayors' salaries, and the number of councillors) depend on whether the municipality is above or below arbitrary population thresholds. Several papers have used a regression discontinuity design (RDD) to measure the effects of these threshold-based policies on political and economic outcomes. Using evidence from France, Germany, and Italy, we highlight two common pitfalls that arise in exploiting population-based policies (confounded treatment and sorting) and we provide guidance for detecting and addressing these pitfalls. Even when these problems are present, population-threshold RDD may be the best available research design for studying the effects of certain policies and political institutions.
Keywords: H10; H19; H70; H77; 330; regression discontinuity design; causal inference; sorting; population thresholds; institutional design